Mega-Deals: What Consequences for SSA?. (9th December 2016) - Guimbard, Houssein; Le Goff, Maëlan
Abstract: The SSA countries are excluded from the mega-deals, free trade agreements (FTA) currently under negotiations between several large economies (EU–USA, EU–Japan, China–Japan–Korea, Trans-Pacific Partnership and ASEAN+6). As SSA exports remain dependent on these large markets, SSA countries could undergo important economic impacts. Using a dynamic Computable General Equilibrium Model, we find that mega-deals would have a negative impact on the welfare of SSA countries. Regional integration (through the negotiation of the 'Tripartite' FTA, which gathers, 26 African countries) might limit these losses, but SSA countries that are not involved still undergo negative consequences. A continental regional trade agreement involving all SSA countries would counterbalance the negative impacts of the mega-deals. We also show that openness of SSA countries towards Asia could be a potential solution to avoid trade diversion.